LEARNING ACADEMIC WRITING IN THE AGE OF AI THROUGH PATTERNING CHATGPT PROMPTED TEXTS: THE HARE VS. THE TORTOISE - Safir, Kassim Boudjelal (Sanata Dharma University, 2024)
The quill is dead; long live AI. Generative AI writing tools or what is commonly known as GAI or GenAI are becoming the students best friends. Today, they are largely used -and abused- by students and surprisingly even researchers looking for the perfect text. Patterning GenAI content like ChatGPT is still an unexplored avenue. From this perspective, this paper tries to provide structured guidance for struggling post-millennial learners. After asking ChatGPT to generate academic texts, a content analysis was conducted to unlock ChatGPT's seemingly perfect writing style. The results of the research uncovered a series of decoded patterns that offer a treasure map and an academic journey to GenAI minds. Furthermore, this showed that (over) relying on GenAI machines or competing with them is simply counter-productive. Therefore, learning WITH them is technically possible. Imagine for a second the great potential of such cooperation human-machine. Speed isallied with imagination. Why not? Moving from a prohibitive approach to an inclusive one through learning with AI chatbots might be a solution.